EFFECT OF RETRIEVAL TECHNIQUES ON THE QUALITY OF ABATTOIR OVARIAN FOLLICULAR OOCYTES IN ASSAM HILL GOATS - BORAH, D; BISWAS, RK; DEKA, BC; SINHA, S; BARKALITA, L; BORAH, RS; NATH, KC; KALITA, MK; DEWRY, RK (The Indian Journal of Animal Reproduction, 2022)
The oocytes recovered (n=2539) from the abattoir collected goat ovaries (n=712) by aspiration, slicing and puncture techniques were washed 4-5 times in a washing medium (36 ml TCM-199, 4 ml Foetal Bovine Serum and 200 μl Gentamicin) and were graded as A, B and C on the basis of their cumulus cell layers surrounding the zona pellucida. The mean recovery rate of oocytes per ovary using slicing technique was higher (4.21±0.08, p
Keywords: Abattoir; Goat; Oocyte; Recovery rate; Slicing